PD-L1 expression as a predictive biomarker for cytokine-induced killer cell immunotherapy in patients with hepatocellular carcinoma. (2nd July 2016) - Chen, Chang-Long; Pan, Qiu-Zhong; Zhao, Jing-Jing; Wang, Ying; Li, Yong-Qiang; Wang, Qi-Jing; Pan, Ke; Weng, De-Sheng; Jiang, Shan-Shan; Tang, Yan; Zhang, Xiao-Fei; Zhang, Hong-Xia; et al.
ABSTRACT: Cytokine-induced killer (CIK) cell immunotherapy represents an effective treatment strategy for treating hepatocellular carcinoma (HCC). However, the therapeutic benefits of CIK cell treatment can be influenced by differences in complex immune microenvironment between patients. Herein, we investigated the relationship between PD-L1 expression and survival benefits of CIK cell immunotherapy in HCC patients. This retrospective study included 448 HCC patients: 217 cases underwent hepatectomy alone; 231 cases received hepatectomy and post-operative CIK cell transfusion. Immunohistochemistry was used to measure PD-L1 expression in tumor tissue sections from all patients. Meanwhile, flow cytometry was performed to explore the relationship between PD-L1 expression and localized inflammatory response in HCC microenvironment. We found a significantly improved prognosis in CIK treatment group compared with surgery alone group. In the CIK treatment group, higher PD-L1 expression was observed in patients who exhibited long-term survival benefit. Survival analysis showed patients with ≥5% PD-L1 expression had better overall survival (OS) and recurrence-free survival (RFS) than patients with 1–5% or <1% PD-L1 expression, particularly in the subgroup with high hepatitis B viral load. By contrast, PD-L1 expression did not show direct impact on the survival of patients in surgery alone group. Additionally, PD-L1 expression was found to be highly associated with hepatitis B viral load and the proportion of tumor-infiltrating lymphocytes in HCC patients. In conclusions, our study indicates that PD-L1 expression may reflect the presence of endogenous host immune response to tumor and serve as a biomarker for predicting survival benefits from adjuvant CIK cell immunotherapy in HCC patients.